ANÁLISIS DE LOS ESTÁNDARES DEL EMPLEO DEL SERVIDOR DE BASE DE DATOS DEL GAD MUNICIPAL DE VENTANAS - JIMENEZ VERGARA, ERNESTO ISRAEL (2019)
The present case study entitled "Analysis of the use standards of the database server of the municipal GAD of Windows", has the purpose of analyzing the application of standards required for the correct use of the managed server in the ICT department of the institution. The reason of this study is to know the main criteria of the application of standards which is routed in two directions, the first is empirical is to say by custom or by the way of working of a person, the second corresponds to compliance with the rules which are provided by various entities through a document which they have called 'standard'. These rules can be used as many times as necessary by the institutions that choose to comply with the requirements provided by that documentation, in order to achieve this purpose it is necessary to gather information that allows a rational analysis, as well as to theoretically substantiate the reasons why it is necessary and useful its application. The analysis of the standards applied or not applied in the server provides the institution with enough knowledge to make decisions; avoid plagiarism, optimize the processes that lead to the attention of a client as well as facilitate the work of the areas that depend on their services. Due to the broad context of the standards, the present study contains a limit in its analysis, that is to say studying only certain regulations considered important and notorious that are required for the use of a server, leaving aside certain problems unless they are indirectly related. with the studied object.